A system for identifying musical notes from an audio and a method therefor - Noordin, Nor Kamariah; Ng, Chee Kyun; Si Toh, Chooi Ling (2012)

(untitled)
The present invention relates to a system (100) for identifying musical notes from an audio comprising an audio receiving component (20) and a musical note identifying component (30) for analyzing the audio data, converting the audio data into a readable element having a plurality of identifiable characteristics, segmenting the readable element into a plurality of segments, and identifying the musical notes with respect to the segments from the readable element based on the identifiable characteristic. The present invention (100) also relates to a method identifying musical notes from an audio.